KETERKAITAN RG-ALJABAR DAN STRUKTUR GRUP - Irwan Yudi (MATEMATIKA FSM, UNDIP, 2014)
In this paper is discussed an algebraic structure which is called RG-algebra. The RG-algebra is a subclass of BCI-algebra and a sub subclass of K-algebra. Therefore, everyRG-algebra is a BCI-algebra, but conversly is not true. The RG-algebra andGroup Structure have a relation. Its relation is RG-algebra can be constructed by acommutativegroup and conversly commutativegroup can be constructed by a RG-algebra. The RG-algebra is a K-algebra with commutativegroupas generator group.